2021
DOI: 10.1093/plcell/koab293
|View full text |Cite
|
Sign up to set email alerts
|

The Chlamydomonas bZIP transcription factor BLZ8 confers oxidative stress tolerance by inducing the carbon-concentrating mechanism

Abstract: Photosynthetic organisms are exposed to various environmental sources of oxidative stress. Land plants have diverse mechanisms to withstand oxidative stress, but how microalgae do so remains unclear. Here, we characterized the Chlamydomonas reinhardtii bZIP transcription factor BLZ8, which is highly induced by oxidative stress. Oxidative stress tolerance increased with increasing BLZ8 expression levels. BLZ8 regulated the expression of genes likely involved in the carbon-concentrating mechanism (CCM): HIGH-LIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Our results suggest that the important role of C/S1 bZIPs in seed development 30,51 may be mediated by hypoxia-related target genes. In fact, the functions of bZIPs in tolerance to oxidative stress can be traced back as early as algae 52 . Since hypoxia responses are also relevant in the context of plant response to submergence 53,54 , we compared the S1 and S1:C targets to genes that are differentially expressed following submergence treatment 55 and observed a much higher level of enrichment of S1 and S1:C targets in submergence-induced genes compared to submergence-repressed genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results suggest that the important role of C/S1 bZIPs in seed development 30,51 may be mediated by hypoxia-related target genes. In fact, the functions of bZIPs in tolerance to oxidative stress can be traced back as early as algae 52 . Since hypoxia responses are also relevant in the context of plant response to submergence 53,54 , we compared the S1 and S1:C targets to genes that are differentially expressed following submergence treatment 55 and observed a much higher level of enrichment of S1 and S1:C targets in submergence-induced genes compared to submergence-repressed genes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, acclimation to low-CO 2 availability needs to include not only activation of CCM to elevate CO 2 levels at the site of fixation, but also of protection against photooxidative damage. It was recently shown that overexpression of the bZIP transcription factor BLZ8, resulting in enhanced CCM via overexpression of HLA3, CAH7, and CAH8, conferred enhanced oxidative tolerance triggered by alkaline stress 57 . Although the qE capacity of the BLZ8 overexpressing lines was not assessed, this work suggests that CCM and protection from oxidative stress are physiologically interconnected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, acclimation to low-CO 2 availability needs to include not only activation of CCM to elevate CO 2 levels at the site of fixation, but also of protection against photooxidative damage. It was recently shown that overexpression of the bZIP transcription factor BLZ8, resulting in enhanced CCM via overexpression of HLA3, CAH7 and CAH8, conferred enhanced oxidative tolerance triggered by alkaline stress 59 . Although the qE capacity of the BZL8 overexpressing lines was not assessed, this work suggests that CCM and protection from oxidative stress are physiologically interconnected.…”
Section: Discussionmentioning
confidence: 99%